Análise de Séries temporais no mercado financeiro como ferramenta de auxílio de investimento - (:unkn) unknown (Universidade Federal do Pampa, 2025)
The financial market is extremely unstable and dynamic, which can make decision-making difficult for new investors. This work addresses concepts of time series analysis and employs forecasting models such as Facebook’s Prophet, LSTM, and ARIMA to support data analysis and decision-making. In addition, a software tool was developed to perform temporal analyses of historical financial asset data. The objective of this study is to develop a tool that evaluates the profit potential of financial assets over the coming months and assists novice investors in their decision-making process through the analysis of historical data and the identification of patterns such as trends and seasonality. The results obtained so far indicate that the forecasting models are capable of capturing the temporal behavior of financial assets, with the LSTM model showing superior predictive performance compared to ARIMA and Prophet, while the latter proved effective in modeling trends and seasonal components. Therefore, the proposed tool demonstrates potential to support the develo
Keywords: Séries temporais; Facebook’s Prophet; LSTM; ARIMA; Mercado Financeiro; Time series; Financial Market; ENGENHARIAS